Finnish waterfowl monitoring results 1986–2025 - Piha, Markus; Ikonen, Katja; Lindén, Andreas; Lehikoinen, Aleksi; Rajala, Tuomas; Seimola, Tuomas (Luonnonvarakeskus, 2025)
The primary goal of the national waterfowl monitoring scheme in Finland is to track changes in breeding population abundances and assess the annual reproductive success of ducks in various types of aquatic habitats. The data are essential for managing waterfowl habitats, regulating hunting, and monitoring biodiversity in wetland ecosystems. The monitoring is coordinated by the Natural Resources Institute Finland and the Finnish Museum of Natural History, with voluntary participation from hunters and birdwatchers. The results indicate that waterfowl populations in Finland have declined overall during the monitoring period 1986–2025. Over the long term (40-year time-series), the breeding populations of most of the 16 monitored species have decreased significantly, with the sharpest declines observed in nutrient-rich (eutrophic) waters. The long-term declines of Northern Pintail (Anas acuta), Northern Shoveler (Spatula clypeata), Eurasian Wigeon (Mareca penelope), Tufted duck (Aythya fuligula), Pochard (Aythya ferrina), Horned Grebe (Podiceps auritus), and Eurasian Coot (Fulica atra) have been particularly steep. In contrast, the population abundance of Black-throated Loon (Gavia arctica), which is typical for nutrient-poor (oligotrophic) lakes, has remained stable, while the Whooper Swan (Cygnus cygnus), which breeds in various wetland types, has increased. Over the past ten years, some waterfowl populations have stabilized or even recovered, especially in northern Finland. For instance, the breeding populations of Common Goldeneye (Bucephala clangula) and Mallard (Anas platyrhynchos) have grown in northern areas, possibly due to climate change affecting species distributions. The results were mixed in terms of reproduction in year 2025. The reproductive success of Mallard and Common Goldeneye improved nationwide compared to 2024, while the breeding success of Eurasian Teal (Anas crecca) and Eurasian Wigeon remained similar to the previous year. In 2023–2025, helicopter surveys conducted as part of the Taiga Bean Goose (Anser fabalis) monitoring program in Lapland and Northern Ostrobothnia also included observations of duck broods. These surveys revealed lower reproductive success in 2025 compared to 2023 and 2024, particularly for Common Goldeneye. The notably poor breeding outcome in northern Finland may be related to a low phase in (typically cyclic) vole population abundances, which likely leads to increased predation pressure on ducks, caused by mammal and avian predators. Overall, the breeding pair numbers of several species increased from 2024, and some species showed above-average reproductive success. Nevertheless, the long-term decline still dominates the observed pattern, especially among species associated with nutrient-rich waters. The causes of waterfowl decline are multifaceted. Some species are especially affected by eutrophication and the brownification of waters due to drainage of surrounding catchment areas. For many species, the abundance of non-native predators is likely a major contributing factor. Wetland restoration remains a key measure for improving the status of waterfowl populations. The results highlight the urgent need for conservation measures, particularly wetland restoration and control of non-native mammal predators.
Keywords: waterfowl; waterfowl surveys; bird monitoring; game ecology; eutrophication